2015
DOI: 10.1007/s11517-015-1421-5
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and classifying three different hand movement types through electroencephalography recordings for neurorehabilitation

Abstract: Brain-computer interfaces can be used for motor substitution and recovery; therefore, detection and classification of movement intention is crucial for optimal control. In this study, palmar, lateral and pinch grasps were differentiated from the idle state and classified from single-trial EEG using only information prior the movement onset. Fourteen healthy subjects performed the three grasps 100 times while EEG was recorded from 25 electrodes. Temporal and spectral features were extracted from each electrode,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
61
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 48 publications
11
61
2
Order By: Relevance
“…Herein, the achieved results (average k score of 0.769% and associated average classification accuracy of 82.13%) are comparable to published results on RP-based binary BCIs: 76% average sensitivity in predicting gross movement from idle state (Lew et al, 2012); 82.21% average classification accuracy in predicting fine movements from idle state (Abou Zeid and Chau, 2015); 76.27% (Lu et al, 2014) and 74.99% (Abou Zeid et al, 2016) average classification accuracies in predicting the laterality of fine movements. Furthermore, the results in this paper are superior to reported performance on multiclass classification of movement related potentials: 59.25% average classification accuracy amongst four different levels and speeds of intended right ankle movements (Jochumsen et al, 2013); 63% average classification accuracy amongst three different grasp tasks (Jochumsen et al, 2015); 73% average classification accuracy amongst two different right angle movements, following detection of movement from rest (Hassan et al, 2015). …”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Herein, the achieved results (average k score of 0.769% and associated average classification accuracy of 82.13%) are comparable to published results on RP-based binary BCIs: 76% average sensitivity in predicting gross movement from idle state (Lew et al, 2012); 82.21% average classification accuracy in predicting fine movements from idle state (Abou Zeid and Chau, 2015); 76.27% (Lu et al, 2014) and 74.99% (Abou Zeid et al, 2016) average classification accuracies in predicting the laterality of fine movements. Furthermore, the results in this paper are superior to reported performance on multiclass classification of movement related potentials: 59.25% average classification accuracy amongst four different levels and speeds of intended right ankle movements (Jochumsen et al, 2013); 63% average classification accuracy amongst three different grasp tasks (Jochumsen et al, 2015); 73% average classification accuracy amongst two different right angle movements, following detection of movement from rest (Hassan et al, 2015). …”
Section: Discussioncontrasting
confidence: 59%
“…In Jochumsen et al (2013), authors achieved average classification accuracy of 59.25% between four different levels and speeds of intended right ankle movements. Another study (Jochumsen et al, 2015) showed the possibility of classifying between three different grasp tasks with an accuracy of 63%. A most recent study (Hassan et al, 2015) showed that, following detection of movement from rest, an average classification accuracy of 73% can be achieved between two different right ankle movements.…”
Section: Introductionmentioning
confidence: 99%
“…However, classification rates for multi-class classification problems are still relatively low in healthy volunteers. As an example, recent studies directed towards the extraction of additional information from movement intention beyond simple detection, such as the prediction of the body part that is about to perform the movement [18], or the classification between different types of movement used in daily life, such as palmar, lateral and pinch grasps [10], resulted in classification accuracies not better than chance levels for the 4-class classification attempts.…”
Section: Neurophysiological Aspects Of Movement Predictionmentioning
confidence: 99%
“…The movement decoding process is generally focused on detecting a predetermined final state and lacks attention regarding the quality of the action, resulting in simple, rough commands [8]. Research on fine movements of body structures such as fingers [9], or complex movement control [10] is comparatively scarce. It is straightforward to hypothesise that better commands can be achieved if movement kinematics and kinetics are taken into account in the decoding process [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation